PENGARUH WORD OF MOUTH, KUALITAS PRODUK, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN ULANG PADA USAHA SUSHI BARI DI BADUNG BALI - Sri Wulaningsih, Ni Made Novi; Mitariani, Ni Wayan Eka; Hendrawan, I Gede Yudhi (Ekonis: Jurnal Ekonomi dan Bisnis, 2025)
Abstract: The culinary business is a business that has great opportunities and promising results for business actors. The development of the culinary business, especially in Bali, is very rapid, this can be seen from the increase in the number of restaurants in Bali every year obtained from data from the Central Bureau of Statistics. This research aims to examine the influence of word of mouth, product quality and service quality on repeat purchase decisions in Sushi Bari business in Badung Bali. In this research, the population is consumers who have shopped at the Sushi Bari business, the number of which is uncertain each year using a sampling technique, namely non-probability sampling. Multiple linear regression analysis techniques were chosen to analyze the data in this study. The results of the research show that word of mouth, product quality and service quality have a positive and significant influence on repurchase decisions. Companies are expected to always pay attention to the quality of the products offered to consumers to increase consumer interest in repurchasing the company, and can always strive for innovation in the products they offer. offered to consumers and maintain the taste of a product to increase repurchase decisions at the Company and always provide the best service to consumers to maintain consumer satisfaction so that repurchase decisions can increase. Keywords: Word of mouth, product quality, service quality, and repeat purchase decisions